Um olhar para as perspectivas sobre a velhice de pessoas com deficiência visual praticantes de goalball - Feck, Roberta Marostega (2021)
Healthy aging alone is a challenge, but associated with some disability it becomes a complex task in a scenario from a personal perspective. The objective was to analyze the personal perspective of old age of people with visual impairment who practice Goalball. The research is of a quantitative nature, characterized as a case study. The participants were selected intentionally, so there was the participation of 19 visually impaired people, who practice Goalball. Of these 11 are men and 8 women with an average age of 36 years. The research site was the Association of the Blind of Rio Grande do Sul (ACERGS), which has the practice of sports. For data collection, a socio-demographic data sheet and a disability data sheet, and the Sheppard Inventory (Neri, 1986) were used. For analysis, a database was created initially composed of numeric and categorical variables. STATA software version 12.1 was used to perform data analysis. The descriptive analysis consisted of the presentation of measures of central tendency as mean and median, measures of dispersion as standard deviation for numerical variables, and the presentation of frequencies and percentages for categorical variables. For the inferences, the t test was applied to compare quantitative variables of independent samples, chi-square association test and fisher's exact test for association between two categorical variables. The value of 5% for the level of significance was considered as a reference and all ethical criteria were respected. All participants agreed to participate in the study by accepting the informed consent form, which was sent via the Google form, and were aware of the objectives and procedures of the present study. From the results there was the production of the article, pointing out that the perceptions of old age in all the analyzed factors were positive. It is also pointed out that some characteristics of the disability, the contextual conditions of the participants, associated with the practice of Goalball, positively influenced the way of seeing old age. It was concluded that in this group, the disability is not a limiter, nor an indicator that foresees an old age marked by negative perceptions, having the practice of Goalball as a potentiator of healthy aging. It is understood that old age is a socially and culturally constructed category, and that there is no single way of aging which depends on the context in which people are inserted. It is also known that the results obtained in this study cannot be generalized, due to the characteristics and peculiarities found. Finally, it is clear that aging with a disability requires adaptations, especially in a society still unprepared for human diversity, but it does not limit and / or prevent old age as a positive phase in life, maturing and visibility.